1993
DOI: 10.4049/jimmunol.150.11.5202
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD25+ and CD25-T cells in acute HIV infection in vitro.

Abstract: T cell activation plays a major role in the ability of the HIV to remain latent or establish a productive infection. The alpha-chain of the IL-2R (CD25, Tac, p55) is expressed on activated but not resting T cells and therefore represents an ideal marker to distinguish activated from resting T cells. The present studies were designed to define the role of CD25+ (activated) and CD25- (resting) T cells in an acute HIV infection in vitro. This objective was accomplished by selectively killing CD25+ cells with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…CD25 is also known as IL-2 receptor. 49 To further investigate if NMN could impact IL-2-induced T cell proliferation and HIV-1 replication, we measured CD25 + and ki67 + cell frequencies among NMN-treated HIV-1-infected CD4 + T cells in the presence of dose-escalating IL-2 on day 4 and day 7 after infection ( Supplementary Figure S8a ). We found that the frequencies of CD25 + and Ki67 + CD4 T cells did not change significantly by IL-2, but that decreased CD25 MFI and increased ki67 MFI were found on day 7 when compared to day 4 ( Supplementary Figure S8b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD25 is also known as IL-2 receptor. 49 To further investigate if NMN could impact IL-2-induced T cell proliferation and HIV-1 replication, we measured CD25 + and ki67 + cell frequencies among NMN-treated HIV-1-infected CD4 + T cells in the presence of dose-escalating IL-2 on day 4 and day 7 after infection ( Supplementary Figure S8a ). We found that the frequencies of CD25 + and Ki67 + CD4 T cells did not change significantly by IL-2, but that decreased CD25 MFI and increased ki67 MFI were found on day 7 when compared to day 4 ( Supplementary Figure S8b ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings pointed to a selective effect of NMN on CD25 + CD4 + T cells. 49 By CyTOF analysis, CXCR3 + effector and CCR4 + central memory CD4 + T cells were found to be two distinguishable subsets affected by the NMN treatment in terms of the CD25 expression. These CXCR3 + effector and CCR4 + central memory CD4 + T cell subsets were of low expression of CCR6.…”
Section: Discussionmentioning
confidence: 96%
“…al. through an in vitro assay shown a signi cant increase in CD25 in PLWHIV (50). By maintaining the expression of CD25, the virus ensures a productive infection (35), however in HIV infection where is perpetuated a repeated stimulation of CD4 + T-cells, also is favored an activation induced cell death (AICD) result of the co-expression of Fas and FasL (51).…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that Gag does not require CD25 to accumulate at the VS, which is consistent with data showing VS formation in CD25-negative cell lines. Interestingly, CD25 expression combined with other activation markers has been shown to predict HIV-1 permissiveness of CD4 + T cells ( 81 , 82 ). Further, regulatory T cells (Tregs), expressing high levels of CD25, have been shown to be susceptible to HIV-1 infection ( 82 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CD25 expression combined with other activation markers has been shown to predict HIV-1 permissiveness of CD4 + T cells ( 81 , 82 ). Further, regulatory T cells (Tregs), expressing high levels of CD25, have been shown to be susceptible to HIV-1 infection ( 82 84 ). Further analyses will elucidate if bacteria-induced CD25-high PBT have also a Treg phenotype.…”
Section: Discussionmentioning
confidence: 99%